Functional and cognitive impairment, social functioning, frailty and adverse health outcomes in older patients with esophageal cancer, a systematic review. Issue 6 (November 2018) - van Deudekom, Floor J.; Klop, Henk G.; Hartgrink, Henk H.; Boonstra, Jurjen J.; Lips, Irene M.; Slingerland, Marije; Mooijaart, Simon P.
Abstract: Background: Older patients with esophageal cancer are at high risk of adverse health outcomes, but the association of geriatric assessment with adverse health outcomes in these patients has not been systematically evaluated. The aim of this systematic review was to study the association of functional and cognitive impairment, social environment and frailty with adverse health outcomes in patients diagnosed with esophageal cancer. Methods: We searched Pubmed, Embase, Web of Science and Cochrane Library for original studies reporting on associations of functional or cognitive impairment, social environment and frailty with adverse outcomes (mortality, functional or cognitive decline, adverse events during treatment, prolonged length of hospitalization (LOS) and health related quality of life (HRQoL)) after follow-up in patients with esophageal cancer. Results: Of 1.391 identified citations, nineteen articles were included that reported on 53 associations. The median sample size of the included studies was 110 interquartile range (IQR 91–359). Geriatric conditions were prevalent: between 14 and 67% of the included participants were functionally impaired, around 42% had depressive symptoms and between 5 and 23% did not have a partner. In nineteen of 53 (36%) associations functional or cognitive impairment or frailty were significant associated with adverse health outcomes, but the studies were small. In four out of six (67%) associations with the largest sample size ( n  ≥ 359), functional impairment or social environment were significant associated with adverse health outcomes. Conclusion: Functional and cognitive impairment, depression and social isolation are prevalent in patients with esophageal cancer, and associate with adverse health outcomes. Geriatric measurements may guide decision-making and customize treatments, but more large studies are needed to explore the clinical usability.